PERANCANGAN PAKAIAN EVENING DRESS BRAND FELICIA MERIDA UNTUK WANITA INDONESIA BERTUBUH PETITE - Felicia Merida; - Enrico (Jurnal Vicidi, 2016)
Indonesian woman are categorized as petite woman with the height below average which is 160 cm. Indonesian fashion brand has mostly been manipulated by the international market. The sizing they offer are mostly sized based on their standard sizing which are different with the standard sizing woman in Indonesia have. A wrong decision when purchasing dress will make petite woman appear to be smaller then they realy are. Here, Felicia Merida offers an evening dress that fits petite woman in Indonesia. A collection with silhouette manipulation, fragments, and jewellery embelishments are added to compliment Indonesian woman with petite body types.